1995
DOI: 10.1002/anie.199525511
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Attack on (π‐Allyl)palladium Complexes: Direction of the Attack to the Central or Terminal Carbon Atom by Ligand Control

Abstract: Strongly stabilized carbon nucleophiles such as dialkyl malonates can also attack the central carbon of (π‐allyl)palladium complexes. The regiochemistry of the reaction (attack at the terminal or C2 carbon atom; see picture) is controlled by the choice of the ligands L in the palladium complex. E = CO2Et, L = PPh3, PtBu3, P(OPh)3, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 35 publications
2
17
0
Order By: Relevance
“…In addition to reactivity at the π-allyl carbon termini, nucleophilic attack at the central carbon of the allyl fragment to afford palladacyclobutane species is known . Previous experimental and computational studies find the mode of reactivity to be highly dependent on the σ-donating/π-accepting nature of the ancillary ligand and the basicity of the nucleophile .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to reactivity at the π-allyl carbon termini, nucleophilic attack at the central carbon of the allyl fragment to afford palladacyclobutane species is known . Previous experimental and computational studies find the mode of reactivity to be highly dependent on the σ-donating/π-accepting nature of the ancillary ligand and the basicity of the nucleophile .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to reactivity at the π-allyl carbon termini, nucleophilic attack at the central carbon of the allyl fragment to afford palladacyclobutane species is known . Previous experimental and computational studies find the mode of reactivity to be highly dependent on the σ-donating/π-accepting nature of the ancillary ligand and the basicity of the nucleophile . Palladacyclobutane complexes have been proposed as mechanistic intermediates in palladium-mediated cyclopropanation reactions, as well as isolated and characterized by X-ray crystallography …”
Section: Resultsmentioning
confidence: 99%
“…In contrast, electron‐deficient ligands tended to produce the spirocyclic 2‐pyrrolidinone 164 f . These results could be attributed to that because the two empty n (non‐bonding) and π * (antibonding) orbitals of π ‐allyl palladium moiety are very close in energy level, [61b–d] electron‐deficient ligand would facilitate lowering the energy level of the π *‐derived empty orbital. Thus the π * orbitals overlapped well with the HOMO of the incoming nucleophile to produce the preferential formation of palladacyclobutane 4.1B (Scheme 78), delivering the spirocyclic 2‐pyrrolidinone 164 f after reductive elimination of the palladacyclobutane.…”
Section: π‐Allyl Palladium Bearing C‐nucleophilementioning
confidence: 99%
“…Hoffmann confirmed the attack of nucleophile on the central carbon of allyl ligand of π-allylpalladium complex by isolation of the reaction intermediate formed by the nucleophilic attack on a π-allylpalladium complex . Bäckvall showed that a nucleophile was favored to attack the terminal carbon of π-allylpalladium complex using a Pd-catalyst with phosphine as ligand, whereas a central carbon-attacked product was given when nitrogen ligand was used . Musco and Santi reported a catalytic version of the cyclopropanation reaction using 1,1′-bis­(diphenylphosphino)­ferrocene (DPPF) as ligand to produce allylation/cyclopropanation products in a ratio of 1.5–6.5:1 .…”
Section: Introductionmentioning
confidence: 96%
“…7 Backvall showed that a nucleophile was favored to attack the terminal carbon of π-allylpalladium complex using a Pd-catalyst with phosphine as ligand, whereas a central carbonattacked product was given when nitrogen ligand was used. 8 Musco and Santi reported a catalytic version of the cyclo-propanation reaction using 1,1′-bis(diphenylphosphino)ferrocene (DPPF) as ligand to produce allylation/cyclopropanation products in a ratio of 1.5−6.5:1. 9 Satake realized cyclopropanation using a neutral Pd-catalyst, asymmetric catalytic version of the reaction was also provided though the allylation/cyclopropanation ratio as well as the ee values were rather lower.…”
Section: ■ Introductionmentioning
confidence: 99%